Stem cell therapy for hepatocellular carcinoma and end-stage liver disease - Mona S. Abdellateif; Abdel-Rahman N. Zekri (Journal of the Egyptian National Cancer Institute, 2023)
Abstract Hepatocellular carcinoma (HCC) is a major health problem worldwide, especially for patients who are suffering from end-stage liver disease (ESLD). The ESLD is considered a great challenge for clinicians due to the limited chance for liver transplantation, which is the only curative treatment for those patients. Stem cell-based therapy as a part of regenerative medicine represents a promising application for ESLD patients. Many clinical trials were performed to assess the utility of bone marrow-derived stem cells as a potential therapy for patients with liver diseases. The aim of the present study is to present and review the various types of stem cell-based therapy, including the mesenchymal stem cells (MSCs), BM-derived mononuclear cells (BM-MNCs), CD34 + hematopoietic stem cells (HSCs), induced pluripotent stem cells (iPSCs), and cancer stem cells. Though this type of therapy achieved promising results for the treatment of ESLD, however still there is a confounding data regarding its clinical application. A large body of evidence is highly required to evaluate the stem cell-based therapy after long-term follow-up, with respect to the incidence of toxicity, immunogenicity, and tumorigenesis that developed in many patients.